2021
DOI: 10.1088/1755-1315/744/1/012088
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton community structure in Cengkok Coastal Water and it’s around, Teluk Banten

Abstract: Cengkok coastal waters of Banten Bay are one of the waters that have many anthropogenic, industrial, and aquaculture activities. Zooplankton would like to become a bioindicator for the water’s condition. This study aimed to analyze the biodiversity and structure of the zooplankton community in waters. The study was carried out, from May to September 2019 at five stations. Data analysis calculating the value of composition, abundance, similarity index, biological index, and PCA. Based on the study obtained, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 2 publications
3
8
0
Order By: Relevance
“…The Bacillariophyceae class dominated the composition of phytoplankton at six stations in the Panjang and Pamujan Besar Islands. This result is in line with the study of [26][27][28][29][30][31][32] stating that phytoplankton generally has High species richness in marine waters coming from the class Bacillariophyceae. Species from the Bacillariophyceae class that appear dominant are different for each station and month.…”
Section: Abundancesupporting
confidence: 91%
See 2 more Smart Citations
“…The Bacillariophyceae class dominated the composition of phytoplankton at six stations in the Panjang and Pamujan Besar Islands. This result is in line with the study of [26][27][28][29][30][31][32] stating that phytoplankton generally has High species richness in marine waters coming from the class Bacillariophyceae. Species from the Bacillariophyceae class that appear dominant are different for each station and month.…”
Section: Abundancesupporting
confidence: 91%
“…Stations 4 -6 have relatively higher abundances than Stations 1 -3. The results of this study are similar to the results of a study conducted by [9], which was carried out on the Cengkok coast (Banten Bay), and found a large number of crustaceans. The total abundance of zooplankton (ind/m3) at each observation station differed from that of phytoplankton.…”
Section: Abundancesupporting
confidence: 90%
See 1 more Smart Citation
“…Several research activities in Banten Bay were carried out, generally based on scientific fields and locations. Some of these research activities are the Physico-chemical conditions of Cengkok coastal waters [3], Bojonegara coastal waters [4], marine waters around Panjang Island and Pamujan Besar [5], plankton in Cengkok coastal waters [6], plankton at Bojonegara coastal waters [7], benthos in Cengkok coastal waters [8], heavy metal in several aquatic organisms [9][10][11][12][13][14], fish biology [15,16], and fish parasites [17]. However, study on zooplankton in this coastal waters has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several research activities were carried out in Banten Bay, including the physical and chemical environmental conditions of the waters at Cengkok Beach and Bojonegara [3,4], plankton at Cengkok Beach [5], benthos at Cengkok Beach [6], heavy metal content in several biotas in the Cengkok Beach area [7][8][9][10][11], fish biology [12,13], and parasites in fish [14]. In addition, several studies have also been [15,16].…”
Section: Introductionmentioning
confidence: 99%